Alternating current flashover voltage of a uniform polluted glass flat insulator under parallel electric discharges effect - Satta, Samia; Bayadi, Abdelhafid; Boudissa, Rabah (International Journal of Electrical and Computer Engineering (IJECE), 2022)
This work presents a study aiming to analyze the development of parallel discharges on insulating surfaces of different sizes uniformly polluted. Moreover, it is aimed to find an equivalence between multiple point-point and plane-plane configurations. The study is carried out under alternating current (AC) voltage. The effects of many parameters on the electric strength of the considered air gap system configurations are presented. These parameters are the length of the creepage distance, the pollution degree and the contaminated surface width. Glass rectangular surface are used for the tests. Finally, a video camera system is used to support this investigation by laboratory observations of the full process of flashover mechanism. The obtained results show that there is a width limit approximately equal to 8 cm beyond which several arcs, parallel, consecutive and independent can develop. This limit represents the minimal electrical performance of the insulation and we did not observe any effect of the volume conductivity on it.